REGULASI EMOSI DALAM MENYELESAIKAN PERMASALAHAN PADA REMAJA - Janah, Maslichah Raichatul (TALENTA, 2015)
AbstractEmotion regulation are well entrenched in vocational students gave a positive significance . From the research that see that future development of adolescents in this age emotions greatly affect its development . So it appears that both the juvenile form of aggression and bullying behavior influenced of low emotion regulation.The  importance  of  emotion  regulation  that  are  embedded  in  the  vocational students  ,  at  an  early  stage  will  help  in  increasing  achievement  motivation  .  Emotion regulation  are  embedded  with  both  the  need  for  help  from  parents  in  doing  good parenting and the existence of a supportive environmentTo  be  able  to  develop  the  analysis  it  is  necessary  to  study  the  effect  of  free school  policy  as  a  management  strategy  in  the  development  of  vocational  schools  in Sukoharjo in order to create the hyuman resources ExcellenceKey word:Emotional Regulation, Problem Solving, adolescents